Identification of major triglycerides causing the clouding of palm olein - Swe, P.Z.; Che Man, Y.; Ghazali, H.M.; Wei, L.S. (Springer-Verlag, 1994)
Clouding was obtained by storing palm olein at 12.5°C for up to 24h and was separated by centrifugation. the fat crystals were collected after washing with cold acetone. The crystals were identified according to their fatty acid and triglyceride composition, carbon number and degree of unsaturation. Palmitic-oleic-palmitic (POP) and palmitic-oleic-stearic (POS) levels were high in the cloud material, especially in that recovered between 15-18 h of storage. The increase in POP and POS concentrations was concomitant with a decrease in the content of palmiticoleic-oleic (POO). The least amount of POO was also obtained in clouds collected between 15-18 h of storage, compared to the original oil sample. The increase of palmitic acid explained that triglycerides conjugated with palmitic acid molecules in their acyl chains could have been crystallized, and crystallization could have taken place in the order of the number of palmitic molecule in the acyl chain. The concentrations of the other triglycerides did not change much throughout the storage period. Further storage caused the composition of the cloud to become similar to that of the original oil sample. © 1994 AOCS Press.